Antidepressant Effect Of Indomethacin In Mice With Ifn Alpha-Induced Depression (Journal of Pharmaceutical Negative Results, 2023)
The present study aimed to investigate the antidepressant property of Indomethacin using an IFN-α-induced depression model in albino mice. The locomotor activity, splash test, forced swimming test, tail suspension, sucrose preference and open field tests were used to evaluate the antidepressant effect of selected drug on albino female mice after induction of stress. The period of immobility in the TST and percentage preference for sucrose solution were recorded. By monitoring brain malondialdehyde (MDA) level, catalase (CAT) activity, and reduced glutathione (GSH) level, the antioxidant potential was assessed. When compared to stressed group, animals that received Indomethacin had considerably shorter immobility times during the TST. Indomethacin treatment also raised the percentage preference for sucrose solution, nearer to the conventional antidepressant, Amitriptyline. Furthermore, Indomethacin remarkably lowered plasma corticosterone and nitrite levels, reduced glutathione levels while considerably reducing the brain’s MDA and catalase activities. However, further studies should be carried out to explore the antidepressant property of Indomethacin clinically.